Roles of sirtuins in the regulation of antioxidant defense and bioenergetic function of mitochondria under oxidative stress. (September 2014) - Wu, Y.-T.; Wu, S.-B.; Wei, Y.-H.
Abstract: In addition to serving as the power house of mammalian cells, mitochondria are crucial for the maintenance of cellular homeostasis in response to physiological or environmental changes. Several lines of evidence suggest that posttranslational modification (PTM) of proteins plays a pivotal role in the regulation of the bioenergetic function of mitochondria. Among them, reversible lysine acetylation of mitochondrial proteins has been established as one of the key mechanisms in cellular response to energy demand by modulating the flux of a number of key metabolic pathways. In this article, we focus on the role of Sirt3-mediated deacetylation in: (1) flexibility of energy metabolism, (2) activation of antioxidant defense, and (3) maintenance of cellular redox status in response to dietary challenge and oxidative stress. We suggest that oxidative stress-elicited down-regulation of Sirt3 plays a role in the pathophysiology of diabetes, cardiac hypotrophy, mitochondrial diseases, and age-related diseases. Besides, the physiological role of newly identified lysine acylation mediated by Sirt5 and its biochemical effects on oxidative metabolism are also discussed. Moreover, we have integrated the regulatory function of several protein kinases that are involved in the phosphorylation of mitochondrial enzymes during oxidative stress. Finally, the functional consequence of the synergistic regulation through diverse protein modifications is emphasized on the maintenance of the bioenergetic homeostasis and metabolic adaptation of the animal and human cells. Together, we have provided an updated review of PTM in mitochondrial biology and their implications in aging and human diseases through an intricate regulation of energy metabolism under oxidative stress.